Context-dependent extinction learning emerging from raw sensory inputs: a reinforcement learning approach - Thomas Walther; Nicolas Diekmann; Sandhiya Vijayabaskaran; José R. Donoso; Denise Manahan-Vaughan; Laurenz Wiskott; Sen Cheng (Scientific Reports, 2021)
Abstract The context-dependence of extinction learning has been well studied and requires the hippocampus. However, the underlying neural mechanisms are still poorly understood. Using memory-driven reinforcement learning and deep neural networks, we developed a model that learns to navigate autonomously in biologically realistic virtual reality environments based on raw camera inputs alone. Neither is context represented explicitly in our model, nor is context change signaled. We find that memory-intact agents learn distinct context representations, and develop ABA renewal, whereas memory-impaired agents do not. These findings reproduce the behavior of control and hippocampal animals, respectively. We therefore propose that the role of the hippocampus in the context-dependence of extinction learning might stem from its function in episodic-like memory and not in context-representation per se. We conclude that context-dependence can emerge from raw visual inputs.